Knowledge and competences of racket sport coaches: What do they think and know? - Del Corto Motta, M.; Barreira, J.; Cortela, C. C.; Galatti, L. R. (International Journal of Racket Sports Science, 2021)
This study analyzed the professional, interpersonal, and intrapersonal knowledge as well as the most important competences to Brazilian coaches who work with four different racket sports (badminton, squash, tennis, and table tennis). A total of 150 coaches (122 men and 28 women) participated in this study, most of whom were tennis coaches (n=68), followed by badminton (n=39), table tennis (n=21), squash (n=17), and more than one racket sport (n=5). For data collection, a socio-demographic questionnaire and the Coaches` Knowledge and Competence Questionnaire (CKCQ) ( Quinaud et. al., 2018 ) were applied. The Wilcoxon test was used to compare the importance and domain attributed by the coaches to the items. In general, knowledge and competences had high scores of attributed importance and perceived domain. However, knowledge of program implementation and evaluation, professional development of coaches and competence to develop the coaching philosophy had the lowest values of perceived domain.